2007
DOI: 10.1007/s12264-007-0046-6
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB 在中枢神经系统损伤和修复中的作用

Abstract: NF-kappaB family is a kind of nuclear factors in B lymphocyte that can bind to the immunoglobulin kappa-chain enhancer and enhance transcriptional activity. NF-kappaB/Rel proteins, as a dimeric transcription factor, control the expression of genes that regulate a broad range of biological processes through canonical and non-canonical pathways. In the central nervous system, NF-kappaB controls inflammatory reactions and the apoptotic cell death following nerve injury. It also contributes to the infarction and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 33 publications
1
30
0
Order By: Relevance
“…Although NF-B has been linked to both neurodegeneration and neuroprotection [76] , most studies have concentrated on the role of NF-B in the pathogenesis of neuropathic pain [77][78][79][80][81] . Nevertheless, studies of inflammatory demyelination in the peripheral nervous system have shown that NF-B and its inhibitor, I-B, are expressed in macrophages and SCs, possibly regulating the demyelination process [82,83] .…”
Section: Proinflammatory Transcription Factorsmentioning
confidence: 99%
“…Although NF-B has been linked to both neurodegeneration and neuroprotection [76] , most studies have concentrated on the role of NF-B in the pathogenesis of neuropathic pain [77][78][79][80][81] . Nevertheless, studies of inflammatory demyelination in the peripheral nervous system have shown that NF-B and its inhibitor, I-B, are expressed in macrophages and SCs, possibly regulating the demyelination process [82,83] .…”
Section: Proinflammatory Transcription Factorsmentioning
confidence: 99%
“…The role of NF-κB in apoptosis remains controversial. NF-κB has been demonstrated to promote cell proliferation and protect the cell from apoptosis [19] . The anti-apoptosis function of NF-κB most likely occurs through suppression of tumor necrosis factor α (TNF-α) signaling [20] .…”
Section: Activation Of Nf-κb-and Caspase-3-dependent Apoptosismentioning
confidence: 99%
“…Inflammatory stimuli activate the IB kinase (IKK) complex, which phosphorylates IB, leading to its ubiquitination and subsequent degradation. IB degradation facilitates translocation of NF-B to the nucleus, thereby regulating the transcription of genes involved in human disorders, including cancer, neurodegenerative disease, and obesity-related metabolic disease (11)(12)(13). NF-B is also involved in cancer-induced cachexia, because intratumoral injection of NF-B inhibitory oligonucleotides prevents cachexia in a mouse tumor model (14).…”
mentioning
confidence: 99%